O095 Cell-based therapies in surgery: a systematic review of the yield and composition of freshly isolated cells obtained from point-of-care devices which mechanically dissociate lipoaspirate. (22nd July 2022) - Liu, P; Gurung, B; Sochart, D; Kader, D; Asopa, V
Abstract: Introduction: Cell-based therapies using lipoaspirate are gaining popularity within surgical fields due to their hypothesised regenerative potential. Several point-of-care lipoaspirate-processing devices have become available to isolate cells for therapeutic use, with published evidence reporting their clinical relevance. However, few studies have analysed the composition of their minimally manipulated cellular products, information that is vital to understand the mechanisms by which these therapies may be efficacious. This review aimed to identify devices using mechanical-only processing of lipoaspirate, their cell yields, viability, phenotype and where available clinical outcomes. Methods: MEDLINE, Embase and PubMed databases were systematically searched on 01/09/21 using relevant keywords. PRISMA guidelines were followed (PROSPERO#CRD42021282041), and level of evidence was assessed using the Oxford Centre for Evidence-Based Medicine guidelines. Information was extracted and analysed to summarise the cellular composition derived from these devices and their clinical outcomes. Results: 2895 studies were screened and a total of 15 articles (11=Level 5 evidence) fulfilled the inclusion criteria. Overall, 13 devices were identified. All the studies reported cell yield for their devices (range 0.005–21×106). 10 reported viability (range 60–98%), 11 performed immuno-phenotypic analysis of the cell-subtypes and 4 investigated clinical outcomes of their cellular products. Only 2 studies reported all four parameters. Conclusion: Although many devices are available to mechanically process lipoaspirate, few have published peer-reviewed literature of their products' composition. Significant heterogeneity in the reporting of these studies makes it difficult to summarise their clinical potential. This review is unable to make any recommendations on the clinical use of these devices. Take-home message: Many point-of-care devices have become available to mechanically process lipoaspirate to form a cellular product for therapeutic use in surgery. However, few have publications on their products' composition which is information required to understand the mechanisms by which these therapies may be efficacious.